Information Frictions, Belief Updating and Internal Migration: Evidence from Ghana and Uganda - Sarah Frohnweiler; Bernd Beber; Cara Ebert (Institute of Labor Economics (IZA), 2022)
Information frictions about the benefits of migration can lead to inefficient migration choices. We study the effects of a randomly assigned information treatment about regional income differentials in Ghana and Uganda to learn about participants' belief updating and subsequent changes in migration intentions and destination preferences. Participants react to the provided information by correcting their destination preferences towards regions with higher incomes, whereas their intent to migrate changes less. Participants' belief updating follows an asymmetric process restricted to individuals who initially underestimated regional differentials. The results suggest that income differentials matter for where to and less whether to migrate.
Keywords: J31; J68; O15; 330; income differentials; migration decision; belief updating